Negative regulation of type I interferon signaling by integrin-linked kinase permits dengue virus replication. - Yi-Sheng Kao; Li-Chiu Wang; Po-Chun Chang; Heng-Ming Lin; Yee-Shin Lin; Chia-Yi Yu; Chien-Chin Chen; Chiou-Feng Lin; Trai-Ming Yeh; Shu-Wen Wan; Jen-Ren Wang; Tzong-Shiann Ho; et al. (PLoS Pathogens, 2023)
Dengue virus (DENV) infection can induce life-threatening dengue hemorrhagic fever/dengue shock syndrome in infected patients. DENV is a threat to global health due to its growing numbers and incidence of infection in the last 50 years. During infection, DENV expresses ten structural and nonstructural proteins modulating cell responses to benefit viral replication. However, the lack of knowledge regarding the cellular proteins and their functions in enhancing DENV pathogenesis impedes the development of antiviral drugs and therapies against fatal DENV infection. Here, we identified that integrin-linked kinase (ILK) is a novel enhancing factor for DENV infection by suppressing type I interferon (IFN) responses. Mechanistically, ILK binds DENV NS1 and NS3, activates Akt and Erk, and induces NF-κB-driven suppressor of cytokine signaling 3 (SOCS3) expression. Elevated SOCS3 in DENV-infected cells inhibits phosphorylation of STAT1/2 and expression of interferon-stimulated genes (ISGs). Inhibiting ILK, Akt, or Erk activation abrogates SOCS3 expression. In DENV-infected mice, the treatment of an ILK inhibitor significantly reduces viral loads in the brains, disease severity, and mortality rate. Collectively, our results show that ILK is a potential therapeutic target against DENV infection.